Sclerostin Regulation, Microarchitecture, and Advanced Glycation End‐Products in the Bone of Elderly Women With Type 2 Diabetes. (2nd October 2020) - Piccoli, Alessandra; Cannata, Francesca; Strollo, Rocky; Pedone, Claudio; Leanza, Giulia; Russo, Fabrizio; Greto, Valentina; Isgrò, Camilla; Quattrocchi, Carlo Cosimo; Massaroni, Carlo; Silvestri, Sergio; Vadalà, Gianluca; et al.
ABSTRACT: Increased circulating sclerostin and accumulation of advanced glycation end‐products (AGEs) are two potential mechanisms underlying low bone turnover and increased fracture risk in type 2 diabetes (T2D). Whether the expression of the sclerostin‐encoding SOST gene is altered in T2D, and whether it is associated with AGEs accumulation or regulation of other bone formation‐related genes is unknown. We hypothesized that AGEs accumulate and SOST gene expression is upregulated in bones from subjects with T2D, leading to downregulation of bone forming genes ( RUNX2 and osteocalcin ) and impaired bone microarchitecture and strength. We obtained bone tissue from femoral heads of 19 T2D postmenopausal women (mean glycated hemoglobin [HbA1c] 6.5%) and 73 age‐ and BMI‐comparable nondiabetic women undergoing hip replacement surgery. Despite similar bone mineral density (BMD) and biomechanical properties, we found a significantly higher SOST ( p = .006) and a parallel lower RUNX2 ( p = .025) expression in T2D compared with non‐diabetic subjects. Osteocalcin gene expression did not differ between T2D and non‐diabetic subjects, as well as circulating osteocalcin and sclerostin levels. We found a 1.5‐fold increase in total bone AGEs content in T2D compared with non‐diabetic women (364.8 ± 78.2 versus 209.9 ± 34.4 μg quinine/g collagen, respectively; p  < .001). AGEs bone content correlated with worse bone microarchitecture, including lower volumetric BMD ( r = −0.633; p = .02), BV/TV ( r = −0.59; p = .033) and increased trabecular separation/spacing ( r = 0.624; p = .023). In conclusion, our data show that even in patients with good glycemic control, T2D affects the expression of genes controlling bone formation ( SOST and RUNX2 ) . We also found that accumulation of AGEs is associated with impaired bone microarchitecture. We provide novel insights that may help understand the mechanisms underlying bone fragility in T2D. © 2020 American Society for Bone and Mineral Research (ASBMR).